1996
DOI: 10.1590/s0101-81751996000400008
|View full text |Cite
|
Sign up to set email alerts
|

Anomalias e patologias dentárias em Arctocephalus G. Saint-Hilaire & Cuvier (Pinnipedia, Otariidae) da costa do Rio Grande do Sul, Brasil

Abstract: ABSTRACT. TooTH ANOMALlES ANO PATHOLOGIES lN AnCTOCEPHALUS G. SAINT-HI-LAIRE & CUVIER (PlNNIPEDIA, OTARIIOAE) DF RIo GRANDE DO SUL COAST, BRAZIL. The studied species wereArclocephalusauslralis (Zimmennann, 1783) and Arclocephalus tropicalis (Gray, 1872), (five specimens Df each one). Anomalies were discussed under the lighl of lheories which relate lhe ancestry of pinnipeds with lhe Ursidae; as well as concerning lhe evolulionary trends supposed for the Otariidae. Pathologies were related to alimentary and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
(3 reference statements)
0
11
0
6
Order By: Relevance
“…Supernumerary teeth in Otariids possibly represent a reversion to the primitive dentition of terrestrial carnivores, according to the phylogenetic relationships of Pinnipeds (DREHMER & FERIGOLO 1996, DREHMER et al 2004, CRUWYS & FRIDAY 2006. DREHMER et al (2004) reported supernumerary teeth in mandibular PC/6, which represents the atavic reappearance of the lower second molar in some specimens of O. flavescens, reconstructing the origins of Pinnipedimorpha evolution in the Oligo/Miocene (BERTA & WYSS 1994, DREHMER et al 2004.…”
Section: 7mentioning
confidence: 99%
See 4 more Smart Citations
“…Supernumerary teeth in Otariids possibly represent a reversion to the primitive dentition of terrestrial carnivores, according to the phylogenetic relationships of Pinnipeds (DREHMER & FERIGOLO 1996, DREHMER et al 2004, CRUWYS & FRIDAY 2006. DREHMER et al (2004) reported supernumerary teeth in mandibular PC/6, which represents the atavic reappearance of the lower second molar in some specimens of O. flavescens, reconstructing the origins of Pinnipedimorpha evolution in the Oligo/Miocene (BERTA & WYSS 1994, DREHMER et al 2004.…”
Section: 7mentioning
confidence: 99%
“…Maxillary supernumerary teeth have been described in Otariid species in different positions (MILES & GRIGSON 1990, DREHMER & FERIGOLO 1996, DREHMER et al 2004, ABBOTT & VERSTRAETE 2005. As no pinniped ancestor has more than four pre-molars and two molars, totalizing the six post-canine teeth (DREHMER et al 2004), the appearance of maxillary supernumerary teeth in A. tropicalis also does not seem to have any evolutionary or phylogenetic implication.…”
Section: 7mentioning
confidence: 99%
See 3 more Smart Citations